Pengaruh Online Promotion dan Shopping Lifestyle terhadap Perilaku Impulsive Buying Produk Fashion Jiniso di Shopee (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This quantitative research analyzes the influence of online promotion and shopping lifestyle on impulsive buying of jiniso fashion products on the Shopee e-commerce platform. The phenomenon of increased impulsive purchasing behavior is driven by online promotion strategies (discounts, vouchers, flash sales) and a tendency towards a consumptive shopping lifestyle. The population for this study comprises all individuals who have purchased Jiniso fashion products on Shopee, with a sample of 100 respondents determined using a non-probability sampling technique. Primary data were collected through online questionnaires via Google Forms, while secondary data were obtained indirectly from intermediary sources such as literature, articles, journals, and websites related to the research object. Based on SPSS test results, all research instrument indicators were found to be valid and reliable. Partial t-tests revealed that both online promotion and shopping lifestyle variables significantly influence impulsive buying. Furthermore, the F-test indicated that both independent variables simultaneously affect impulsive buying. Among the two variables, online promotion emerged as the dominant variable. The conclusion shows that online promotion and shopping lifestyle significantly impact impulsive buying behavior for Jiniso fashion products on Shopee, providing implications for fashion businesses to maximize online promotions and adapt marketing strategies to effectively increase sales.